The Degree of Ajloun Governorate School Principals Practice of Educational Leadership standers from teacher perspective - AlGharibeh, Mohammad Mahmoud AbdAllah (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of Ajloun Governorate school principals practice of educational leadership standers from teacher perspective, the researcher used the Descriptive approaches, to collect data Questioner used, which consisted (33) paragraph Divided to five sector It was applied to an intentional sample of (430) male and female teachers. The results showed that the degree of public school principals’ practice of educational leadership standards from the teachers’ point of view obtained a total arithmetic mean (3.79 out of 5), that is, with a (high) degree of practice at the level of the five domains; The field of decision-making obtained the highest average (4.00), followed by the field of promoting community partnership with an average (3.93), thirdly, the field of human and material resources management with an average (3.92), all with a degree of practice (high), and fourthly, the field of promoting student learning with an average (3.67) and finally planning and evaluation with an average ( 3.43 and these two have a degree of practice (medium)The finding also showed there is no statistically significant differences at (α≤0.05) refers to teacher sex (male and female) in addition there were statistically significant differences between the teacher years of experience in favor of (9 years and more).
Keywords: degree of practice; School Principals; Educational Leadership standers; Ajloun; teacher perspective